Pancreatic Agenesis with Congenital Diaphragmatic Hernia and Congenital Heart Disease: A Case Report - Atsushi Nakao; Tomohiro Takeda; Yoshiya Hisaeda; Atsushi Hirota; Syusuke Amagata; Yuko Sakurai; Tadashi Kawakami (Thieme Medical Publishers, Inc., 2013)
Abstract Pancreatic agenesis is a rare disease that causes neonatal diabetes mellitus and exocrine pancreatic insufficiency. We report the case of a very low birth weight infant with congenital diaphragmatic hernia, and congenital heart disease (ventricular septal defect and patent ductus arteriosus). Failure to gain weight, despite well-managed respiratory and heart failure, was improved by infusion of subcutaneous insulin, administration of pancreatic enzyme, and nutrition of medium-chain-triglyceride -enriched formula. This is the first case of pancreatic agenesis with both malformations where the patient is discharged from the hospital. Early diagnosis and adequate treatments to compensate pancreatic function may prevent mortality and improve growth.